TRIB3 promotes malignancy of head and neck squamous cell carcinoma via inhibiting ferroptosis - Li Chen; Wanzun Lin; Haojiong Zhang; Shikai Geng; Ziyu Le; Fangzhu Wan; Qingting Huang; Huaiyuan Chen; Xingyu Liu; Jiade J. Lu; Lin Kong (Cell Death and Disease, 2024)
Abstract Tribbles pseudokinase 3 (TRIB3) has been identified recently as a novel oncogene in several cancers. Still, further extensive research is imperative to elucidate its function and the molecular mechanisms underlying its involvement in the progression of head and neck squamous cell carcinoma (HNSCC). In our study, we found that TRIB3 silencing significantly promoted cell death by inducing ferroptosis. The interaction of TRIB3 with Transcription Factor 4 (TCF4) and β-catenin created a heterotrimeric complex, which directly interacts with the ALOXE3 promoter, detrimentally impacting its activation. The consequential partial neutralization of ferroptosis induced by TRIB3 deficiency is observed through the implementation of ALOXE3 knockdown. Furthermore, the study demonstrated that the molecular inhibitor hesperidin, targeting TRIB3, not only reduced cell malignancy but also induced ferroptosis, thereby suppressing tumor growth. Overall, our findings unequivocally validate the proposition that TRIB3 deficiency precipitates the iron death mechanism, thereby indicating that the strategic targeting of TRIB3 could emerge as an innovative therapeutic strategy for HNSCC.